Capital Structure Impact On The Human Capital Investment: Eastern European Countries Case - KHOUJA, Imen; BELKHIRIA, Sina; TLILI, Ons (Archives of Business Research, 2021)
Among growth factors of a company, its human capital, because of its hardly imitable trait. However, investing in human capital is intangible and risky, which makes its funding arduous. This article considered the impact of the company’s capital structure on the human capital investment decision through training using probit regressions. Among a sample of SMEs from 24 Eastern European countries, the results confirmed that bank loans foster trainings. However, an increase in self-financing slows down such investments.